Experimental study on gamma ray induced light output deterioration in LaBr3:Ce scintillator - Lu, Yi; Song, Zhaohui; Li, Gang; Weng, Xiufeng; Yi, Yicheng; Yu, Xiaoren; Jiang, Haoyu; Cui, Zengqi; Hu, Yiwei; Zhang, Guohui (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2020)
In this paper, the effects of dose and dose rate on the light output of LaBr3:Ce scintillator are studied in detail. The relative light output of the crystal is measured in real time by measuring the photoelectric current of the detector during irradiation at a 137Cs irradiation facility. It is found that the light output of the LaBr3:Ce scintillator continues to decrease with the increase in dose. Permanent radiation damage in LaBr3:Ce is also observed at a cumulative dose of 100kGy.